2019
DOI: 10.1111/jfd.12979
|View full text |Cite
|
Sign up to set email alerts
|

First detection and isolation of infectious haematopoietic necrosis virus from farmed rainbow trout in Nyeri County, Kenya

Abstract: Infectious haematopoietic necrosis virus (IHNV) is the causative agent of infectious haematopoietic necrosis, a disease of salmonid responsible for great economic losses. The disease occurs in most parts of the world where rainbow trout is reared but has not been previously reported in Kenya. In this study, rainbow trout fry and growers from two farms in Nyeri County were screened for IHNV. Whole fry (n = 4 from each farm) and kidney samples from growers (n = 15 and n = 6 from the two farms, respectively) were… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(2 citation statements)
references
References 35 publications
0
2
0
Order By: Relevance
“…e Economic Stimulus Programme (ESP) of 2009 brought with it increased fish farming in Kenya, and at the same time, new challenges unfolded including limited knowledge of aquaculture management practices, nutritional requirements for optimal fish productivity and biosecurity [1], and occurrence and spread of fish diseases [2,3]. In Nyeri County, fish farming is both commercial and subsistence with many farmers primarily practicing subsistence farming for family consumption.…”
Section: Introductionmentioning
confidence: 99%
“…e Economic Stimulus Programme (ESP) of 2009 brought with it increased fish farming in Kenya, and at the same time, new challenges unfolded including limited knowledge of aquaculture management practices, nutritional requirements for optimal fish productivity and biosecurity [1], and occurrence and spread of fish diseases [2,3]. In Nyeri County, fish farming is both commercial and subsistence with many farmers primarily practicing subsistence farming for family consumption.…”
Section: Introductionmentioning
confidence: 99%
“…Aquaculture has been touted as a promising solution for food insecurity, poverty and malnutrition in Kenya (Ogello and Munguti 2016), and indeed the Government of Kenya continues to invest heavily towards the intensification of aquaculture. Unfortunately, in the recent times, some of the most infectious diseases which can cause serious losses in farmed fish, some up to 90% such as Tilapia Lake Virus (TiLV) (Matolla 2020), Infectious Pancreatic Necrosis (Mulei et al 2018) and the Infectious Haematopoietic Necrosis Virus (IHNV) the causative agent of infectious haematopoietic necrosis, a disease of salmonid responsible for great economic losses (Mulei et al 2019) have all been reported infecting fish in Kenya and Uganda. It is important to note that the country's aquaculture production has been reported to be in a short fall of the required demand, hence imports such as those from China, and for us to have a true expansion in production, adequate fish health management is critical (Børge 2018).…”
Section: Biosecurity Measuresmentioning
confidence: 99%